The Level Of Mass Media Usage and The Role Of Communication Of Cattle Farmers Group Members in Cattle Supervisory Communication Network - A. Saleh (Jurnal Komunikasi Pembangunan, 2008)
The cattle agribusiness supervision activities, similar to other types of supervision are supposed to undergo a communication structure changes. The communication pattern is no longer in the form of "oil droplets" supervision having a top down outline, or relying on the LAKU supervision system which has a dyadic pattern integrating the top down and bottom up interest with an interpersonal or group communication approach. However turning into participation and exchange of knowledge and experiences through "farmer as partner" communication pattern, therefore the advance technology and local traditions are forming synergy. It is suspected that the cattle farmer communication pattern in cattle supervision no longer relies on interpersonal.